2019
DOI: 10.1108/jaoc-09-2018-0090
|View full text |Cite
|
Sign up to set email alerts
|

A review of literature on IFRS in Africa

Abstract: Purpose This paper is an appraisal of existing literature on IFRS in Africa. In a bid to determine what exists and what is missing in the literature, the authors have reviewed three streams of studies, namely, adoption, compliance/harmonisation and consequences of IFRS in Africa, with the aim to suggest what remains to be investigated on IFRS in Africa. Design/methodology/approach This paper uses a systematic review approach including synthesis of a variety of archival materials. Articles on Africa were summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 82 publications
0
11
0
Order By: Relevance
“…Research networks have never been discussed in previous studies, either by Wahyuni et al (2020), Tsalavoutas et al (2020), or Tawiah and Boolaky (2019). Therefore, this study differed from the previous research.…”
Section: Collaboration Networkmentioning
confidence: 67%
See 3 more Smart Citations
“…Research networks have never been discussed in previous studies, either by Wahyuni et al (2020), Tsalavoutas et al (2020), or Tawiah and Boolaky (2019). Therefore, this study differed from the previous research.…”
Section: Collaboration Networkmentioning
confidence: 67%
“…In Indonesia, the research was conducted by Wahyuni et al (2020). Similar research was also carried out by Tawiah and Boolaky (2019) and Balsari and Varan (2014) abroad. Previous studies have shown the contrast results, so it is debatable whether the presence of IFRS can complement, improve, and perfect the quality of accounting standards.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Of course, IFRS reviews are not new, as there are reviews on IFRS adoption (De George et al, 2016;Khlif & Achek, 2016), on single standards (Merz, 2017), IFRS adoption in the singled out region (Jang et al, 2016;Tawiah & Boolaky, 2019) as well as the impact of IAS/IFRS on quality of financial reporting (Wadesango et al, 2016). Having said that however it should be noted that all these papers use a completely different methodology, which contrasted those papers and our study.…”
Section: Literature Reviewmentioning
confidence: 74%